Hello,
I think I have the concept but when I get to the end of the problem I cannot figure out what to do. I read my book and I think I missed something some where... Here is what I have so far.
2x³+3x²= 8x+12
- 8x+12 =-8x+12
2x³+3x²- 8x+12=0
2x²(x+1) 4(2x+3)
x-1=0 2x²-4 (2x+3)??? help
please
Something in the last two line are wrong. The answer is {-2, -3/2, 2} I just can't figure out how to get there.
I think I have the concept but when I get to the end of the problem I cannot figure out what to do. I read my book and I think I missed something some where... Here is what I have so far.
2x³+3x²= 8x+12
- 8x+12 =-8x+12
2x³+3x²- 8x+12=0
2x²(x+1) 4(2x+3)
x-1=0 2x²-4 (2x+3)??? help
Something in the last two line are wrong. The answer is {-2, -3/2, 2} I just can't figure out how to get there.